2020
DOI: 10.1089/aid.2020.0106
|View full text |Cite
|
Sign up to set email alerts
|

CD4+:CD8+ T Cell Ratio Normalization and the Development of AIDS Events in People with HIV Starting Antiretroviral Therapy

Abstract: We identify factors associated with the normalization of the CD4+:CD8+ T cell ratio among UK Collaborative HIV Cohort study participants, and describe the association of the CD4+ and CD8+ T cell counts and the CD4+:CD8+ T cell ratio, with the risk of new AIDS events among individuals who achieve a suppressed viral load. Participants initiating combination antiretroviral therapy (cART) after 2006 with a CD4+:CD8+ T cell ratio <1, and viral suppression within 6 months were included. Cox proportional hazard model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Certainly, late presentation status was found to have a negative impact on both the absolute CD4 cell count and CD4/CD8 ratio recovery, as observed in other studies [ 18 , 19 ]. Besides, we found that the risk of clinical progression, and specifically of AIDS events, was higher when the CD4/CD8 ratio was ≤ 0.4 over time for both non-late and late or advanced presenters.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Certainly, late presentation status was found to have a negative impact on both the absolute CD4 cell count and CD4/CD8 ratio recovery, as observed in other studies [ 18 , 19 ]. Besides, we found that the risk of clinical progression, and specifically of AIDS events, was higher when the CD4/CD8 ratio was ≤ 0.4 over time for both non-late and late or advanced presenters.…”
Section: Discussionsupporting
confidence: 78%
“…This corroborates the role of the CD4/CD8 ratio as prognostic marker of clinical outcomes in PLWH no matter how they present at diagnosis. Although this marker has previously shown an association with the development of AIDS- and non-AIDS-related events in some cohorts of PLWH [ 8 , 9 , 16 18 ] to the best of our knowledge this is the first study evaluating its role among late and advanced presenters and assessing whether its clinical impact is the same among the non-late presenters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effectiveness of cART, the CD4 + /CD8 + ratio does not always normalize in patients with HIV, especially in those with late start of treatment (deferred group) and low initial CD4 + /CD8 + T-cell ratio. Early diagnosis should be encouraged so that patients are treated as soon as possible (promptly), favoring a more robust immunological reconstitution [15][16][17] . Although a low CD4 + / CD8 + ratio is an indicator of CD4 + T cell lymphopenia and CD8 + T cell activation 18,19 , in this study, a lower result for this ratio was not associated with non-AIDS events, which may be associated with some independent comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, HIV causes severe immune dysregulation, characterized by systemic depletion of CD4+ T cells, increased HIV-1 specific CD8+ T cells, inflammation and a progressive failure of the immune system[13]. Initiation of ART has been shown to augment HIV-specific CD4+ T cell responses, but normalization of the CD4:CD8 T cell ratio does not occur in a large proportion of HIV positive individuals[4]. In pregnant women living with HIV (PWLWH), pregnancy is not associated with HIV disease progression, although it has been associated with functional impairment of systemic effector T cells and an overall altered response against HIV control[5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In adults, HIV causes severe immune dysregulation, characterized by systemic depletion of CD4+ T cells, increased HIV-1 specific CD8+ T cells, inflammation and a progressive failure of the immune system [1][2][3]. Initiation of antiretroviral therapy (ART) has been shown to augment HIV-specific CD4+ T cell responses, but normalization of the CD4:CD8 T cell ratio does not occur in a large proportion of people with HIV [4]. In pregnant women living with HIV (PWH), there is evidence that women who initiate ART before pregnancy are more likely to have adverse birth outcomes compared to initiation during pregnancy [5].…”
Section: Introductionmentioning
confidence: 99%